BENTUK PENYAJIAN TARI CAKALELE PADA PENOBATAN KEPALA DUSUN SUKU BURU DI PROVINSI MALUKU - Nur Rahmatia; Riana Diah Sitharesmi; Mimy A. Pulukadang; Nurlia Djafar; La Ode Karlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Cakalele dance is a traditional war dance originating from Maluku Province. In the inauguration ceremony of the village head, the Cakalele dance is performed as the fourth sequence in the traditional ritual procession. In the Buru tribal language, the village head is called “Kepala Soa.” This study aims to explain the process of the Kepala Soa’s inauguration and to describe the presentation form of the Buru Tribe’s Cakalele dance during this event in Maluku Province. The Cakalele performed at the inauguration ceremony is classified as a ritual dance. This study employed a qualitative descriptive method. Data collection techniques included observation, interviews, and direct observation of the presentation form of the Cakalele dance during the Kepala Soa’s inauguration, which was documented through photographs and video recordings. The analysis results show that the Cakalele dance is performed by two male dancers who must meet specific requirements: they must be members of the Buru tribe, married, have previously performed the Cakalele dance, and be physically and mentally healthy. The costume worn consists of a “lenso” (scarf), a plain black shirt and pants, and a red cloth (merat). The Cakalele dance comprises three primary movement motifs and is accompanied by the traditional Tifa drum. The main property in the dance is the Pattimura sword. The performance takes place in the front yard of the Oki Baru Village Office.